2008
DOI: 10.1590/s0066-782x2008001800004
|View full text |Cite
|
Sign up to set email alerts
|

A influência do plano de saúde na evolução a longo prazo de pacientes com infarto agudo do miocárdio

Abstract: SummaryBackground: Little is known, especially in our country, about the influence of health insurance plans on the long term outcome of patients after acute myocardial infarction (AMI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Similar to our findings, Nicolau et al [ 11 ] compared the mortality rates during and after hospital admission in patients with acute myocardial infarction who benefited from the private or the public healthcare system. These authors demonstrated that the public healthcare patients exhibited the same in-hospital mortality rate (10.3% versus 11.4%; P = 0.5) but also exhibited an increased chance of long-term mortality (36% higher odds; P = 0.005) compared with the private healthcare patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our findings, Nicolau et al [ 11 ] compared the mortality rates during and after hospital admission in patients with acute myocardial infarction who benefited from the private or the public healthcare system. These authors demonstrated that the public healthcare patients exhibited the same in-hospital mortality rate (10.3% versus 11.4%; P = 0.5) but also exhibited an increased chance of long-term mortality (36% higher odds; P = 0.005) compared with the private healthcare patients.…”
Section: Discussionsupporting
confidence: 90%
“…Patients who use the public healthcare system are more likely to have less education and income. These factors, in association with a poor organizational health structure, could limit the access of ICU survivors to healthcare [ 11 ]. An Australian cohort of 15619 critically ill patients demonstrated that those with the worst SEC were also younger and had more severe conditions and that the long-term mortality among this group was also higher despite the in-hospital mortality of these patients being similar to the patients with better SEC [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…26, 27 Moreover, work in other countries has suggested that patients enrolled in public health care plans may not fare as well as patients who are privately insured. 28 However, these studies either did not distinguish between effects due to payer status and effects due to SES, nor they did not control for risk factors commonly associated with low SES. Since payer status and SES tend to be highly correlated, this represents an important confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data from major societies point cardiovascular diseases as those with increased mortality and morbidity [1,2]. There is expectation that in 2020, 40% of deaths are related to them.…”
Section: Introductionmentioning
confidence: 99%